1992
DOI: 10.1021/ma00038a031
|View full text |Cite
|
Sign up to set email alerts
|

Novel multifunctional initiators for polymerization of 2-oxazolines

Abstract: Polymerization of 2-oxazolines was carried out using bifunctional and tetrafunctional initiators. Allyl-type dihalides and xylylene dihalides were used as bifunctional initiators. The allyl-type dihalides employed are l,4-dibromo-2-butene and 3-iodo-2-(iodomethyl)-1-propene and the xylylene dihalides are pxylylene diiodide and p-, m•, and o-xylylene dibromides. The degree of polymerization (DP) of the resulting polymer was very close to the feed ratio of the monomer to initiator. From a kinetic study, it was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 6 publications
2
46
2
Order By: Relevance
“…ZnCMPP was prepared by refluxing a mixture containing CMPP and Zn(CH 3 COO) 2 in chloroform/methanol for 1 h. We confirmed that CMPP without halogen exchange by NaI did not initiate the polymerization at 60°C in acetonitrile at all, even when the reaction time was increased to 48 h. In contrast, the polymerization of 2-methyl-2-oxazoline occurred when CMPP or ZnCMPP was used as initiator associated with NaI [8,9] (in situ exchange of Cl with I by adding NaI to the reaction mixture). As reported by Kobayashi et al [8], a higher feed ratio of oxazoline to multihalogene initiator not only increases the average molecular weight of the polymer but also promotes the star shape formation.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…ZnCMPP was prepared by refluxing a mixture containing CMPP and Zn(CH 3 COO) 2 in chloroform/methanol for 1 h. We confirmed that CMPP without halogen exchange by NaI did not initiate the polymerization at 60°C in acetonitrile at all, even when the reaction time was increased to 48 h. In contrast, the polymerization of 2-methyl-2-oxazoline occurred when CMPP or ZnCMPP was used as initiator associated with NaI [8,9] (in situ exchange of Cl with I by adding NaI to the reaction mixture). As reported by Kobayashi et al [8], a higher feed ratio of oxazoline to multihalogene initiator not only increases the average molecular weight of the polymer but also promotes the star shape formation.…”
Section: Introductionsupporting
confidence: 53%
“…For polymers 1-3, however, the values of M n determined by GPC (DMF as eluent, polystyrene as standard, with RI detector) were lower than those evaluated by 1 H NMR, and M n (by GPC) for 3 is only 1.5 times that for 1 ( Table 1). This is often seen in the case of star-shaped polymers owing to the lowered hydrodynamic diameter [8,9,14]. In addition, polymers 1 and 2 showed relatively narrow polydispersity, the value being 1.3.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…[18] Some reports on star homo-and block coPOx can be found. [19][20][21][22] However, only two reports investigated whether all functionalities of a multifunctional initiator are of equal reactivity. In these cases, a step-wise initiation by the plurifunctional initiators, halogen and tosylate, was observed.…”
Section: Communicationmentioning
confidence: 99%
“…The outer block, poly(2-ethyl-2-oxazoline) (PEtOx), is water-soluble and non-toxic, and the pseudo-peptide character of this material has been shown to induce similar "stealth" behavior, as observed for PEO [19,22,[37][38][39]. PEtOx can be synthesized with a wide range of functional groups, being present via cationic ring-opening polymerization (CROP) [40][41][42][43]. We used different lengths of the outer PEtOx blocks, and the obtained [PEO 28 -b-PEtOx x ] 8 materials were characterized via size exclusion chromatography (SEC), nuclear magnetic resonance spectroscopy (NMR) and Fourier-transform infrared spectroscopy (FT-IR).…”
Section: Introductionmentioning
confidence: 99%